Visual Arts Work
XXIV, 267 p. 43 illus., 42 illus. in color.
Keywords: This book provides the most comprehensive picture to date of work in the visual arts ecosystem in Australia. In a context where artists’ incomes are consistently low and falling, commercial galleries are financially vulnerable, and public galleries face program funding challenges — this book explores barriers to the economic health of the sector, the challenge of improving artists’ and arts workers’ working conditions, and the realities of being a creative in the twenty-first century. The book combines an analysis of art world economic value chains alongside alternative and emergent cultural, social and political economies with new quantitative and qualitative insights from artists and arts workers. With interdisciplinary methodologies and industry engagement, it examines multiple and hybrid systems of value and includes the perspectives of visual artists, craft artists and arts workers with diverse lived experiences. Our research offers greater insight into the social, cultural, and political forces that underly the mediation of art to the public including an urgent emphasis on gender, cultural safety and care work including the concerns of First Nations artists, culturally and linguistic diverse artists, and artists with disability. Our approach unpacks the diversity and hybridity of art ‘work’ to include practices realised through digitisation, internationalisation, community engagement and intersectoral partnerships. Grace McQuilten is Professor at the School of Art, RMIT, Australia. Chloë Powell is Research Assistant at the School of Art, RMIT, Australia. Marnie Badham is Associate Professor at the School of Art, College of Design and Social Context, RMIT, Australia. Kate MacNeill is Associate Dean, Faculty of Arts, University of Melbourne, Australia. Jenny Lye is Associate Professor at the Department of Economics, University of Melbourne, Australia.